Auditing the accounts of research and exploration stage in accordance with the financial reporting standard (6) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The oil and gas production industry is considered the most important industries in the modern world because of its large relative significance among the group of energy recourses required for the world, where the natural resources represent the oil and natural gas fields, phosphate, gold, coal, forests and others. The most important advantage of the natural resources is its need for huge financial investments for a relatively long period of time from the beginning of the work until the start of extracting natural resources. Also, there are numerous cases where the natural source is not feasible exploited economically and is not discovered until after the passage of a long period of time from the start of work and paying relatively high amounts of money. The research aims to develop a proposed program to audit the activity of research and exploration for natural resources and evaluating them according to the financial reporting standard No. (6) and to show the impact of the application of this standard on the data of the sample company to determine any of the exploration and evaluation expenditure that must be recognized as an asset and which should be recognized as an expense as well as the extent of the disclosure of financial statements based on the international standard No. (6) for research and exploration expenses for the purpose of knowing the financial position of the company.